2019
DOI: 10.5469/neuroint.2019.00150
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Clinical Diagnosis and Genetic Analysis of Hereditary Hemorrhagic Telangiectasia in South Korea: Multicenter Case Series and a Systematic Review

Abstract: Purpose: Hereditary hemorrhagic telangiectasia (HHT), a rare genetic vascular disorder, has been rarely reported in South Korea. We investigated the current prevalence and presenting patterns of genetically confirmed HHT in South Korea. Materials and Methods: We defined HHT patients as those with proven mutations on known HHT-related genes (ENG, ACVRL1, SMAD4, and GDF2) or those fulfilling 3 or 4 of the Curaçao criteria. A computerized systematic search was performed in PubMed and KoreaMed using the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In our cohort of Japanese patients, the ENG mutations were dominant ( ENG / ACVRL1 ratio at 1.35) although the difference was smaller as compared with our own previous smaller series [ 19 ]. Previous reports showed a considerable difference in the incidence of ENG - vs ACVRL1 -HHT with the ENG dominance in the US ( ENG / ACVRL1 at 1.58) [ 27 ], Netherlands (3.40) [ 17 ], Denmark (4.05) [ 15 ], and Korea (1.47) [ 17 ] as opposed to the ACVRL1 dominance in France and Italy (0.37) [ 28 ], Germany (0.89) [ 29 ], and China (0.41) [ 18 ]. The founder effects could be one of the explanations for these differences although it is unclear whether the previously identified, small-sized founder effects could account for all these differences [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort of Japanese patients, the ENG mutations were dominant ( ENG / ACVRL1 ratio at 1.35) although the difference was smaller as compared with our own previous smaller series [ 19 ]. Previous reports showed a considerable difference in the incidence of ENG - vs ACVRL1 -HHT with the ENG dominance in the US ( ENG / ACVRL1 at 1.58) [ 27 ], Netherlands (3.40) [ 17 ], Denmark (4.05) [ 15 ], and Korea (1.47) [ 17 ] as opposed to the ACVRL1 dominance in France and Italy (0.37) [ 28 ], Germany (0.89) [ 29 ], and China (0.41) [ 18 ]. The founder effects could be one of the explanations for these differences although it is unclear whether the previously identified, small-sized founder effects could account for all these differences [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, more than 1000 different mutations have been identified as associated with ENG -HHT and ACVRL1 -HHT [ 12 , 13 ]. However, most of the large-scale studies have been conducted on Caucasians [ 1 , 14 – 16 ], and only limited, relatively small studies have been reported for other populations [ 17 19 ]. Moreover, even within Caucasians, the reported mutational spectrum has been different depending on the countries so does the clinical presentation [ 14 – 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, no features of HHT were reported in these patients (14,15). Meanwhile, a recent multicenter case series investigating the genetic analysis of HHT in Korea reported that among 49 patients who had underwent genetic testing, 28 had ENG mutations and 19 had ACVRL1 mutations, while the other two patients were all negative for ENG, ACVRL1, and SMAD4 mutations (16). Similarly, a study in Chinese families with HHT revealed variants in ACVRL1 and ENG, while no SMAD4 mutations were detected (17).…”
Section: A B a Bmentioning
confidence: 94%
“…AVMs can also be associated with inherited genetic disorders such as HHT and capillary malformation–AVM (CM–AVM) [ 21 22 23 ]. All HHT mutations ( ENG , ACVRL1 , SMAD4 , and GDF2 ) appear to cause decreased BMP-Smad signaling that may lead in turn to increased angiogenesis, otherwise CM–AVM has loss-of-function mutations in RASA1 (CM–AVM1) and EPHB4 (CM–AVM2) genes, leading to activation of Ras-MAPK pathway [ 22 24 25 ]. Cerebral AVMs can also occur as a component of syndrome-associated malformations, such as the Parkes–Weber syndrome, which is characterized by multifocal CMs, high-flow shunt lesion, and limb overgrowth, or congenital lipomatous overgrowth, vascular malformations, epidermal nevis, spinal/skeletal anomalies/scoliosis (CLOVES) syndrome [ 12 ].…”
Section: Composition Of An Rnvd Panel and Prevalence Of Each Disease In Koreamentioning
confidence: 99%
“…F, G. A pulmonary arteriovenous fistula (arrows) was demonstrated on the chest CT (F) and confirmed on the pulmonary arteriography (G) in the proband's father. The pedigree (A) is adapted from Kim et al Neurointervention 2019;14:91–98 [ 25 ]. AVF = arteriovenous fistula, AVM = arteriovenous malformation, DM = diabetes mellitus, ICH = intracranial hemorrhage…”
Section: Figmentioning
confidence: 99%